Desmoplastic small round cell tumour of the uterus: a case report - Nur Zaiti Md Arshad; Mohd Rushdan MN; Lee, SJ (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Desmoplastic small round cell tumour (DSRCT) is a very rare malignant tumour which commonly presented as an intraabdominal tumour. It has a distinct histological and immunophenotypic characteristic which differentiates it from other types of small blue cell tumour such as Ewing’s sarcoma, primitive neuroectodermal tumour, neuroblastoma and malignant mesothelioma. Apart from the abdomen, it may also originate from other region of the body including the reproductive organs.